An Important Moment in the History of Latin American Artistic Criticism of the Second Half of the Twentieth Century: the Austin Symposium (1975) - Nuez Santana, José Luis de la (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
This paper focuses on the content analysis of the debates on Latin American art and literature held at the Austin symposium, United States, in October 1975. The purpose of this study is to contextualize culturally the debates and to distinguish the different critical orientations in the artistic world, both among Latin Americans and Americans and among the Latin American artists and critics themselves.
Keywords: Latin American contemporary art; Latin American art criticism; identity; art and politics; avant-garde